Laser scattering, optical constants and connection to other material performances (Kerr constant, mobility/diffusion coefficient/electrophoresis and depolarization) - Sreckovic, Milesa; Tistchenko, An Marie; Jevtic, Sanja; Kaludjerovic, Branka; Pelemis, Svetlana; Zarubica, Katarina; Zarubica, Veljko (Journal of Engineering & Processing Management, 2019)
Scattering of optical photons from the view of parallel methods related to absorption, scattering, fluorescence, reflection with inclusion of the polarization states of laser beams from experiment and theory give many possibilities for obtaining indirect data on material, processes, and dynamics. As a method with minimal perturbations, if low power beams are involved, certain type of data is provided. In fundamental dependences of various material properties, many phenomenological and basic laws are covered. Several coupled variables, primarily with the processes of scattering, pointing out further possibilities for linking the obtained theoretical or experimental results were presented. By including simulations, this associates with biological environments / variables for properties equivalent to defined tissues, cells, and characteristics. Along with selected formalisms including Stokes vectors and scattering matrices, a biological cell as an object can be monitored in time and influence of various environments could be predicted. Connecting Kerr’s effect with depolarization and scattering makes the complete description of molecule possible. Angular scattering observation with experimental possibilities gives the fastest practical data. This enables interpretation of E. coli with the application of Stokes vector formalisms. A relatively small number of material constants for many simulation cases could give draft estimation, but the experiment depends on the measuring devices and samples. The necessary symmetries showing the size of the scattering centers are analyzed, with the scattering data for some liquids (known / less known). From measured data, depolarization could be calculated, and with refractive index (molar refraction) connection with Kerr effect/ birefringence for selected solutions and behavior of molecules could be monitored. From the experimental Rayleigh factors, cross section (apparent/ effective) and attenuation coefficients for pure liquids were calculated. An approach for the correct assessment of the measurement uncertainty in the process of calibration of polyethylene samples.